2019
DOI: 10.1016/j.matbio.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Matrix modeling and remodeling: A biological interplay regulating tissue homeostasis and diseases

Abstract: The overall structure and architecture of the extracellular matrix undergo dramatic alterations in composition, form, and functionality over time. The stochasticity begins during development, essential for maintaining organismal homeostasis and is heavily implicated in many pathobiological states including fibrosis and cancer. Modeling and remodeling of the matrix is driven by the local cellular milieu and secreted and cell-associated components in a framework of dynamic reciprocity. This collection of expertl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 201 publications
(147 citation statements)
references
References 140 publications
(130 reference statements)
0
144
1
2
Order By: Relevance
“…The present study revealed that, compared with normal prostate, both low-grade and high-grade PCa have decreased expression of many ECM and plasma membrane proteins, which form large putative PPI networks. The ECM remodeling is probably due to increased proteolysis by matrix metalloproteinases and extracellular vesicles [59]. The most striking difference between low-grade and high-grade PCa is that only small PPI networks were more abundant in the former group, whereas a large PPI network was upregulated in the latter group.…”
Section: The Putative Ppi Network Of Depsmentioning
confidence: 99%
“…The present study revealed that, compared with normal prostate, both low-grade and high-grade PCa have decreased expression of many ECM and plasma membrane proteins, which form large putative PPI networks. The ECM remodeling is probably due to increased proteolysis by matrix metalloproteinases and extracellular vesicles [59]. The most striking difference between low-grade and high-grade PCa is that only small PPI networks were more abundant in the former group, whereas a large PPI network was upregulated in the latter group.…”
Section: The Putative Ppi Network Of Depsmentioning
confidence: 99%
“…A hallmark of decorin bioactivity is the dual property of being anti-angiogenic (13,15,27,32,86,87) and pro-autophagic (18,20,28, [46][47][48]. Moreover, the Dcn gene itself is an autophagic-inducible gene (88).…”
Section: Decorin Evokes Intracellular Degradation Of Vegfa Via Autophmentioning
confidence: 99%
“…In some cases, proenzymes are associated with TIMP (low concentration) for correct activation; for example, the MMP-14/TIMP-2/proMMP-2 ternary complex. MMPs may be associated with other ECM components, such as proteoglycans and GAGs, leading to their specific localization in the cellular perimeter or at ECM sites distant from the cell secretion point (Van den Steen et al, 2001;Hernandez-Barrantes et al, 2002;Ra and Parks, 2007;Gabison et al, 2009;Hadler-Olsen et al, 2011;Piperi and Papavassiliou, 2012;Rietz and Spiers, 2012;Li et al, 2014;Arpino et al, 2015;Karamanos et al, 2019).…”
Section: Mmp Familymentioning
confidence: 99%